2018
DOI: 10.1101/317388
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

PLK1 plays dual roles in centralspindlin regulation during cytokinesis

Abstract: Cytokinesis starts in anaphase with the formation of an actomyosin-based contractile ring at the equatorial cortex, which is governed by the local activation of the small GTPase RhoA. Here we delineated the contributions of PLK1 and Aurora B to RhoA activation and cytokinesis initiation in human cells. Knock-down of PRC1, which disrupts the spindle midzone, revealed the existence of two pathways that can initiate cleavage furrow ingression. One pathway depends on a well-organized spindle midzone and PLK1, whil… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 70 publications
1
10
0
Order By: Relevance
“…How Cdk1 activates Plk1 is still unclear, but the Aurora kinases are possible intermediaries, as Cdk1 phosphorylates the Aurora binding partner Bora (also called SPAT‐1) to promote Aurora A activation and phosphorylation of Plk1 in C. elegans and human cells . However, Aurora A ( AurA ) mutants are homozygous viable throughout larval development, do not prevent mitotic entry and instead only cause mild delays in mitotic entry, spindle assembly and asymmetric cell division , while Aurora B loss of function primarily affects cytokinesis and may act in parallel with Plk1 by directly phosphorylating the kinesin MKLP1/KIF23/ZEN4/Pav , which enables it to undergo oligomeric clustering with RacGAP1/MgcRacGAP/CYK4/Tum at the spindle midzone and nearby plasma membrane to promote Pbl/ECT2 recruitment to the plasma membrane and Rho‐driven cleavage furrow formation in cytokinesis . Thus, while much is known about the molecular mechanisms governing Pbl/ECT2 and Rho‐mediated contractility by Aurora B and PLK1 via the central spindle in cytokinesis, our understanding of the upstream cell cycle regulation of Pbl/ECT2 and Rho during mitotic rounding is far more limited.…”
Section: Resultsmentioning
confidence: 99%
“…How Cdk1 activates Plk1 is still unclear, but the Aurora kinases are possible intermediaries, as Cdk1 phosphorylates the Aurora binding partner Bora (also called SPAT‐1) to promote Aurora A activation and phosphorylation of Plk1 in C. elegans and human cells . However, Aurora A ( AurA ) mutants are homozygous viable throughout larval development, do not prevent mitotic entry and instead only cause mild delays in mitotic entry, spindle assembly and asymmetric cell division , while Aurora B loss of function primarily affects cytokinesis and may act in parallel with Plk1 by directly phosphorylating the kinesin MKLP1/KIF23/ZEN4/Pav , which enables it to undergo oligomeric clustering with RacGAP1/MgcRacGAP/CYK4/Tum at the spindle midzone and nearby plasma membrane to promote Pbl/ECT2 recruitment to the plasma membrane and Rho‐driven cleavage furrow formation in cytokinesis . Thus, while much is known about the molecular mechanisms governing Pbl/ECT2 and Rho‐mediated contractility by Aurora B and PLK1 via the central spindle in cytokinesis, our understanding of the upstream cell cycle regulation of Pbl/ECT2 and Rho during mitotic rounding is far more limited.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that PLK1 negatively regulates PRC1 through phosphorylation of a single site, Thr‐602, near the C terminus of PRC1 in mitosis [23]. PLK1 activity promotes the release of centralspindlin from the spindle midzone through inhibition of PRC1 [22]. PRC1 is an anaphase‐specific binding partner for PLK1 and prematurely recruits PLK1 to the spindle during prometaphase and blocks mitotic progression, and depletion of PRC1 by siRNA disrupted the localization of PLK1 to the central spindle [30].…”
Section: Discussionmentioning
confidence: 99%
“…Interaction between centralspindlin and PRC1 is crucial for central spindle formation [21]. Inhibition of PLK1 prevents centralspindlin localization from the spindle midzone [22], and PLK1 negatively regulates PRC1 to prevent premature midzone formation before cytokinesis [23]. Thus, PLK1 may promote the release of centralspindlin from the spindle midzone through inhibition of PRC1 [22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 14-3-3 proteins cross-link and stabilize MKLP1-complexes at the central spindle [125]. PLK1 also plays a role in modulating the availability of centralspindlin to Aurora B through its role in central spindle organization [126]. Thus, the two major structural pathways for central spindle formation involving PRC1 and centralspindlin are linked together by the regulatory network formed by CDK1, Aurora B and PLK1.…”
Section: Phosphatase Switches Regulate Plk1 and Aurora B In Mitotic Exitmentioning
confidence: 99%